Communication Strategy in the Mappetuada Tradition (A Case Study of Macege Urban Village, West Tanete Riattang Subdistrict, Bone District) - Ega Setyawan; Kurniati Abidin (Palakka : Media and Islamic Communication, 2020)
AbstractThis paper discusses the Communication Strategy in the Mappetuada Tradition (A Case Study of Macege Urban Village, West Tanete Riattang District, Bone Regency). The objective of this study is to determine the communication strategies used in the Mappetuada tradition in Macege Village, West Tanete Riattang Sub-District, Bone Regency and to find out the process of resolving differences of opinion between the two parties in the Mappetuada. This study employed field research by conducting study through interviews, observation and documentation. The sources of data in this study are speakers, cultural figures, and also priest. The data collected were analyzed using qualitative descriptive analysis techniques. The results exposed, 1) There are three strategies used in the Mappetuada, namely the religious approach, cultural approach, and artistic approach. 2) Differences of opinion between the two parties in Mappetuada are very rarely encountered because previously the speaker had been given a briefing related everything that would be discussed, especially in Macege. Even if there is a solution, mediation can be carried out by matching thr data by the speakers and asking the two parties of the family to take part in discussing the problem. Keywords: Communication; Mappetuada; Strategy.